Design a wireless antenna for smart tv application / Nor Fazlia Ishak@Isa - Ishak@Isa, Nor Fazlia (2012)
This paper present the dual U-shape microstrip patch antenna feed by the transmission line. The proposed antenna is designed by FR4 substrate and ground plane area 22mmx28mm. The idea of u slot antenna is taken from [3] and improved by adding the Defected Ground Structure (DGS) to improve the radiation pattern. A Rectangular Defected Ground Structure is added at the ground plane to increase the main lobe radiation pattern for the directional antenna and reduce the side lobe radiation pattern. Beside of the new method added into the design, this antenna size is smaller than [3]. The bridge is introduced to increase the gain of the antenna. In chapter 2, the literature review was studied. Many of the microstrip antennas were design by the authors and they are using u-slot and DGS method at the ground. The U-slot antenna is used to increase the bandwidth of the antenna. It is proved from the article written by [2] that u slot antenna can wider the bandwidth with the coaxial feeding method. In this design, the u slot method is introduced to wider the bandwidth but unfortunately with the feeding line method this technique is not applicable to improved the bandwidth. The bridge technique can improve the gain of the antenna. It is written in the [3] and it is proved from my design. The result is shown in the chapter 3. Besides that, the DGS technique is used in this design. It can improve the antenna radiation pattern by increasing the main lobe radiation pattern and reduce the side lobe radiation pattern. The result is shown in the chapter 3. It is proved that DGS technique can changed the current distribution of the antenna. In chapter 3, the analysis effect of the DGS is study and simulated. The comparison between conventional antenna and with DGS antenna is measured. The result of SI 1, radiation pattern, gain, resonance frequency and current distribution were analyzed. The measurement of actual and simulation is also compared and the different was analysis. Beside of focus on 2.45GHz antenna, purposed antenna also can operate in multiband antenna.